The effect of the high intensity interval training on endothelial function concentrating on alterations in miR-16 expression, total antioxidant capacity and serum malondialdehyde in the obese men - Hamidreza Zolfi; Amir Shakib (Fiyz̤, 2022)
Background: Endothelial dysfunction, caused by obesity, can be regarded as the initial step in the development of the cardiovascular disease. Hence, the current study aimed to the effects of HIIT exercises on miR-16 induced endothelial function, total antioxidant capacity (TAC) and serum malondialdehyde (MDA) in the obese men. Materials and Methods: 24 obese male volunteers, with a mean age of 44 years and BMI>30, were randomly divided into the training and control groups. The eight-week HIIT training group did circular exercises, including (Long Knee, Butterfly, Burpy, kettlebell snatch, and Scott Goblet), with an intensity of 80-90 % of Karvonen heart rate (first four weeks: three sessions and second four weeks: four sessions per week). Blood samples were taken from the subjects 48 hours before and after the last training session to analyze miR-16, NO, serum MDA, and TAC indices of the subjects. Results: Eight weeks of HIIT training in the training group caused a significant increase in NO and TAC values and a significant decrease in serum MDA compared to the pre-test values. (P<0.05). Furthermore, compared to the control group, a significant decrease in miR-16 and MDA levels was observed and a significant increase in serum NO and TAC was observed in the training group (P<0.05). Conclusion: HIIT training apparently alter serum NO levels by affecting miR-16 levels and reducing oxidative stress caused by obesity and can prevent from outbreak and development of the cardiovascular disease by improving endothelial function.